2014 IEEE 40th Photovoltaic Specialist Conference (PVSC) 2014
DOI: 10.1109/pvsc.2014.6925340
|View full text |Cite
|
Sign up to set email alerts
|

Industrially feasible all-purpose metal-wrap-through concentrator solar cells

Abstract: The authors combine a silicon-based metal-wrap-through architecture with a unit cell designed for the purpose of operating under concentrated irradiance, called AP-MWT solar cell. On the illuminated side, the negative polarity is electrically separated by using an emitter window surrounding the perimeter of each unit cell. The final solar cell device consists of an arbitrary number of unit cells with sizes ranging from 1 × 2.25 cm2 up to 14 × 13.5 cm2. The Czochralski based bulk material as well as the manufac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Fellmeth et al made the metal wrap through (MWT) cell for concentration using industrial crystalline silicon solar cell manufacturing process, the efficiency was larger than 20% under 5-12 suns [78]. The MWT cell was a combination of bifacial contact cell and back contact cell, the grids were made on the front surface of the cell, but the bus-bars were made on the back surface and connected to grids through the roles in the cell to decrease the shading losses [57,[78][79][80], the structure of the MWT cell drew by Lohmüller et al is shown in Fig. 11 …”
Section: Back Contact Cellmentioning
confidence: 99%
“…Fellmeth et al made the metal wrap through (MWT) cell for concentration using industrial crystalline silicon solar cell manufacturing process, the efficiency was larger than 20% under 5-12 suns [78]. The MWT cell was a combination of bifacial contact cell and back contact cell, the grids were made on the front surface of the cell, but the bus-bars were made on the back surface and connected to grids through the roles in the cell to decrease the shading losses [57,[78][79][80], the structure of the MWT cell drew by Lohmüller et al is shown in Fig. 11 …”
Section: Back Contact Cellmentioning
confidence: 99%
“…The challenge of high currents and metal shading in silicon PV has led to the development of metal‐wrap‐though (MWT) technologies in which the emitter and base contacts are both realised on the rear side of the device. Insulated holes are filled with metal to transport the electric current from the front to the back side where both contacts are isolated and collected in an interdigitated metal grid . This technology has led to Si solar cells with an efficiency up to 21.0% (AM1.5 g) .…”
Section: Introductionmentioning
confidence: 99%